(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
This article aims to identify three fundamental paradigms orienting the interpretative analysis in matters related to children’s health. The normative analysis concerns both the international and the supranational regulations and focuses on the norms of law n. 219 allowing a reconstruction of the fundamental principles in the sector of the children’s right to health. At national level, the analyzed areas are those of informed consent and shared planning of cares. These areas of protection constitute an instrument for verifying the reasonableness of the mentioned paradigms, such as the identity, the relational and the balance between protection and autonomy needs of children, which have emerged at international and supranational level and have been upheld by the principles of the national law n. 219/2017.